Premières réflexions sur la préfiguration d’un observatoire lyonnais du climat - Didier Soto; Florent Renard; Emmanuel Thimonier-Rouzet (EchoGéo)
Adaptation to climate change is ideal for observation. Promising projects, coming from researchers, practitioners and business partners, have been initiated earlier on the metropolitan territory. Now, they require an operational structure to gather and share knowledge and skills. To undertake this partnership approach, a prospective study has been initiated. In this paper, two issues are specifically mentioned: the establishment of this observatory in relation to the needs of practitioners and researchers, and the potential objectives of such an observatory.